If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(7 + x) = 2x + 21 (7 * 3 + x * 3) = 2x + 21 (21 + 3x) = 2x + 21 Reorder the terms: 21 + 3x = 21 + 2x Add '-21' to each side of the equation. 21 + -21 + 3x = 21 + -21 + 2x Combine like terms: 21 + -21 = 0 0 + 3x = 21 + -21 + 2x 3x = 21 + -21 + 2x Combine like terms: 21 + -21 = 0 3x = 0 + 2x 3x = 2x Solving 3x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 3x + -2x = 2x + -2x Combine like terms: 3x + -2x = 1x 1x = 2x + -2x Combine like terms: 2x + -2x = 0 1x = 0 Divide each side by '1'. x = 0 Simplifying x = 0
| 11x=26 | | 187=2.8t+0.5(-.0209625668)t^2 | | -2(10x+3)= | | 8x=3.5 | | (5x+2)+(x+3)= | | -8(2x+6)-(x+7)= | | 6(n-3)+2=2n+4(n-1) | | 29r=3(r^2+4) | | 12x-9x=15 | | 5x-1=-7 | | 3x^4-243=0 | | x(5x-2)=-3 | | x(5x-2)=3 | | 5x+6=23 | | 3x=2x+25 | | 3.3x=2.2x+5.5 | | x/(-2)=7 | | -8t=34 | | (c^3+2c^2d+cd^2)=0 | | X-8=40 | | 13-x=-3 | | 5-4x+5x=6x-12 | | z+1=-17 | | 4x^2+2x+7=0 | | 0.3x+0.4(10)=0.2(x+20) | | x-54=-7 | | 4x=s+5x | | x/10+2=18 | | 2x=5x-3y | | 2(3.14)=5x-3y | | 5.8+1.3n=2.29 | | (y-1)+y=11 |